Trolleys and Transplants: Derailing the Distinction Between Doing and Allowing - Duncan, Emma (De Ethica, 2015)
Two key elements in Judith Jarvis Thomson’s most recent response to the famed Trolley Problem produce a tension that threatens to undermine her account. First, in a reversal of part of her 1985 position, Thomson now argues that a bystander is not permitted to divert a threat. Second, her use of the Doctrine of Doing and Allowing (DDA) to explain intuitions about the permissibility of threat diversion conflicts with her constraint of an agent’s available options to the present tense, which is designed to prevent past bad acts from justifying bad acts in the present. I contend that the conflict between DDA and the tense constraint creates an inconsistency in Thomson’s current position and supports the conclusion that no one, including the trolley driver, is permitted to turn the trolley. In order to resolve this conflict, Thomson must either abandon one of the core features of her explanation or reject a fundamental intuition driving the Trolley Problem, that the driver may divert the trolley to save lives.